PSYCHOSOCIAL ASPECTS OF CONFLICTUAL INTERACTION AMONG PERSONS WITH DISABILITIES IN CONTEMPORARY SOCIETY - Shandruk, Serhiy (Personality and environmental issues, 2026)
This article presents a theoretical analysis of the psychosocial aspects of conflictual interactions involving persons with disabilities in contemporary society. The relevance of the study stems from the need to comprehend the factors that complicate interpersonal interactions of persons with disabilities amid the expansion of inclusive practices, while social barriers, stigmatization, and discriminatory attitudes persist. It is established that conflictual interaction among persons with disabilities is a complex psychosocial phenomenon shaped by the influence of external social conditions and internal psychological mediators. Key social factors identified include stigmatization, discrimination, environmental barriers, paternalistic attitudes, and negative prior interaction experiences. Among the psychological mediators highlighted are self-respect, anxiety, fear of rejection, trust or distrust towards others, and emotional self-regulation. The interaction of these factors contributes to manifestations of conflictual behavior such as hurt feelings, misunderstandings, defensive reactions, avoidance of contact, as well as overt or covert conflicts. The primary consequences of conflictual interactions are outlined, including emotional exhaustion, social isolation, diminished trust, passivity, and self-isolation. The study emphasizes the importance of psychological support, assertiveness development, fostering an inclusive culture, and strengthening social support as critical resources for constructive conflict resolution. A structural-functional model of the psychosocial aspects of conflictual interaction among persons with disabilities is proposed, illustrating the interrelations between social conditions, psychological mediators, manifestations, consequences, and coping resources. The article concludes that conflictual interaction involving persons with disabilities is a multi-level phenomenon that requires comprehensive psychological and social understanding.